Symptoms and sources of Yersinia enterocolitica-infection: a case-control study - Huovinen, Elisa (BioMed Central, 2010)
BACKGROUND: Yersinia enterocolitica (YE) is the causative agent of yersiniosis. YE encompass strains of diverse pathogenicity: YE biotypes 1B and 2-5 are considered pathogenic, whereas biotype 1A is in general considered nonvirulent. Also YE-like species, which can sometimes be misidentified as YE, are considered nonvirulent. METHODS: In order to study differences in clinical picture caused by different YE types and their possible sources a case-control study was conducted in 2006. In this case-control study, 295 case-patients with YE or YE-like finding and their 758 controls responded to the questionnaire about symptoms and possible sources of infection. RESULTS: Strains of pathogenic YE bio/serotypes 3-4/O:3 or 2/O:9 were found in 18%, YE biotype 1A in 65% and YE -like strains of 17% of the patients. Patients infected with the strains of pathogenic YE bio/serotypes were younger and had fever more often than those with BT 1A who suffered more from vomiting. Symptoms of reactive arthritis were reported by 10% of pathogenic YE infections, 3% of YE BT 1A, and 0.3% of the controls. Eating or tasting raw or medium done pork was a significant risk factor for pathogenic YE bio/serotype infection (OR 6.6; 95% CI 1.7-24.9) as well as eating in a canteen (OR 3.5; 95% CI 1.6-7.9). Imported fruits and berries were associated with increased risk of YE BT 1A finding. CONCLUSIONS: The symptoms of the patients with YE BT 1A differed from yersiniosis caused by the classic pathogenic YE bio/serotypes. In addition, the patients with YE BT 1A had more protracted gastrointestinal disorders and unspecific complaints. Small children were overrepresented in classic pathogenic bio/serotypes while in BT 1A or YE-like species were not found among children younger than two years. This suggests the lacking virulence of the BT 1A strains. We can not, however, rule out the possibility that some strains of genetically heterogeneous group of BT 1A may cause an illness.